Classificação das universidades mundiais em 2024 - Hervé Théry (Confins)
A previous article published in the Mappemonde journal had analyzed the Academic Ranking of World Universities (Arwu), mapped its data to reveal the geography of the world's leading universities and other rankings were also analyzed and mapped. The publication of the 2024 edition of the Arwu ranking list provides an opportunity to take stock of its development, map its results once again and compare them with those of other rankings, such as those of Times Higher Education and the Center for World University Ranking (CWUR).